Tobacco control in India - Shimkhada Riti; Peabody John W. (The World Health Organization, 2003)
Legislation to control tobacco use in developing countries has lagged behind the dramatic rise in tobacco consumption. India, the third largest grower of tobacco in the world, amassed 1.7 million disability-adjusted life years (DALYs) in 1990 due to disease and injury attributable to tobacco use in a population where 65% of the men and 38% of the women consume tobacco. India's anti-tobacco legislation, first passed at the national level in 1975, was largely limited to health warnings and proved to be insufficient. In the last decade state legislation has increasingly been used but has lacked uniformity and the multipronged strategies necessary to control demand. A new piece of national legislation, proposed in 2001, represents an advance. It includes the following key demand reduction measures: outlawing smoking in public places; forbidding sale of tobacco to minors; requiring more prominent health warning labels; and banning advertising at sports and cultural events. Despite these measures, the new legislation will not be enough to control the demand for tobacco products in India. The Indian Government must also introduce policies to raise taxes, control smuggling, close advertising loopholes, and create adequate provisions for the enforcement of tobacco control laws.